A 0.5-V MI-OTA-based shadow universal filter with integrated passband gain compensation and low-pass control for low-frequency applications - Kumngern, Montree; Khateb, Fabian; Kulej, Tomasz; Arbet, Daniel (My University, 2025)
Ultra-low-power active filters have received increasing attention in recent years due to emerging applications such as bio-signal sensing and wearable electronic devices, where they are employed in the analog front-end to eliminate interference noise. This paper presents a novel voltage-mode shadow universal filter based on multiple-input operational transconductance amplifiers (MI-OTAs). The multiple-input functionality of the OTA is implemented using the multiple-input bulk-driven MOS transistor (MIBD-MOST) technique, which enables low supply voltage operation and a wide input voltage swing. Additionally, the use of subthreshold operation contributes to the low-power consumption of the OTA. The proposed shadow filter is implemented using a voltage-mode universal filter, in which the low-pass section is employed to control the natural frequency through an external amplifier. The proposed filter provides both non-inverting and inverting transfer functions of low-pass filter (LPF), high-pass filter (HPF), band-pass filter (BPF), band-stop filter (BSF), and all-pass filter (APF). The circuit was designed and simulated using Cadence Virtuoso, utilizing TSMC’s 65-nm 1P9M CMOS technology. The total silicon area of the MI-OTA measured 148 μm × 89 μm. Operating at a supply voltage of 0.5 V and a cutoff frequency of 31.2 Hz, the filter achieved an overall power consumption of 350 nW. Experimental validation was conducted using a prototype implemented with commercially available LM13700N integrated circuits, confirming the filter’s functionality and effectiveness. The proposed design is well suited for low-voltage, low-power applications, particularly low-frequency bio-signal processing such as EEG and EGG acquisition systems, as well as sensor interface systems.
Keywords: Active filter; Bulk-driven MOS transistor; Frequency-agile filter; Operational transconductance amplifier; Shadow filter; Universal filter